A single-center comparison of our initial experiences in treating penile and urethral cancer with video-endoscopic inguinal lymphadenectomy (VEIL) and later experiences in melanoma cases - Gómez-Ferrer, A.; Collado, A.; Ramírez, M.; Domínguez, J.; Casanova, J.; Mir, C.; Wong, A.; Marenco, J. L.; Nagore, E.; Soriano, V.; Rubio-Briones, J. (Frontiers in Surgery, 2022)
ABSTRACT Background: Video-endoscopic inguinal lymphadenectomy (VEIL) is a minimally invasive approach that is increasingly indicated in oncological settings, with mounting evidence for its long-term oncological safety. Objectives: To present our single-center experience of treating penile and urethral cancer with VEIL, as well as its more recent application in melanoma patients. Methods: We prospectively recorded our experiences with VEIL from September 2010 to July 2018, registering the patient primary indication, surgical details, complications, and follow-up. Results: Twenty-nine patients were operated in one (24) or both (5) groins; 18 had penile cancer, 1 had urethral cancer, and 10 had melanoma. A mean 8.62 ± 4.45 lymph nodes were removed using VEIL and of these, an average of 1.00 ± 2.87 were metastatic; 16 patients developed lymphocele and 10 presented some degree of lymphedema; there were no skin or other major complications. The median follow-up was 19.35 months; there were 3 penile cancer patient recurrences in the VEIL-operated side. None of the melanoma patients presented a lymphatic inguinal recurrence. Conclusions: VEIL is a minimally invasive technique which appears to be oncologically safe and to produce fewer complications than open surgery. However, complications such as lymphorrhea, lymphocele, or lymphedema were not diminished by using VEIL.